The Study of the Component of Dual Vocational Training Management of Voacational College in Sakon Nakhon Province - Jangsuk, Patchakanan; Pengsawat, Waro; Chalakbang, Wannika (Journal of Graduate MCU KhonKaen Campus, 2026)
This research article's primary objective was to study the components of dual vocational education management in educational institutions within Sakon Nakhon Province. The research methodology was divided into two key stages. In the first stage, the researcher synthesized in-depth information from 10 academic documents and related sources to identify the main components of dual vocational education management, using a selection criterion of 60% frequency of occurrence. In the second stage, the selected components were evaluated for their appropriateness and accuracy by five experts. The research instruments consisted of a document synthesis form and a 5-point Likert scale questionnaire. Data analysis was conducted using content analysis along with basic statistics, including frequency, percentage, mean, and standard deviation. The results revealed that all components were deemed appropriate at the highest level. The component with the highest mean was cooperation with business establishments ( = 4.80, S.D. = 0.40), followed by curriculum development ( = 4.65, S.D. = 0.48), instructional management ( = 4.53, S.D. = 0.62), and measurement and evaluation ( = 4.47, S.D. = 0.72), respectively.